Hydroxytyrosol attenuates tunicamycin‐induced endoplasmic reticulum stress in human hepatocarcinoma cells. Issue 5 (18th December 2013) - Giordano, Elena; Davalos, Alberto; Nicod, Nathalie; Visioli, Francesco
<x xml:space="preserve">Abstract</x> Scope Hydroxytyrosol (HT) is a phenolic compound peculiarly abundant in olives and it is being recognized as a protector of LDL from oxidation. In addition to lipid oxidation, one emerging risk factor for cardiovascular disease is ER stress. We tested the effect of HT on the modulation of ER stress in HepG2 cells. Methods and results HepG2 cells were treated with 1 μM and 5 μM of HT and 100 μM lipoic acid (LA) and glutathione—ethyl ester (GSH), for 24 h. Induction of the unfolded protein response (UPR) was initiated by treatment with 2 μg/mL tunicamycin for 4 h. Real time RT‐PCR analyses followed by Western blot and ELISA of different ER stress markers revealed that the protective activities of HT were superior to those of two known thiolic antioxidants, i.e., LA and GSH. Conclusion Mounting evidence indicates the ER as an important target of dietary or pharmacological intervention. In this paper, we report the modulatory activities of physiological concentrations of HT toward ER stress and we shed some light on pathways alternative to the well‐known antioxidant mechanisms, through which olive oil phenolics modulate cell signaling and could impact cardiovascular health and degenerative diseases.